Paulo Freire as Learning Theorist - John Holst (Adult Education Research Conference, 2019)
I defend the thesis that Paulo Freire had a theory of learning. Contrary to what learning theorists sustain, I present a theory of learning in Freire’s work.
Keywords: adult learning; dialectics; Freire; lifelong education; praxis